EPISTEMOLOGI IRFANI DALAM PENAFSIRAN AYAT-AYAT MA‘RIFATULLAH: STUDI KRITIS TERHADAP PEMIKIRAN AL-GHAZALI - Wathani, Muhammad Fadhil (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This study examines the epistemology of irfani in Al-Ghazali's thought and its relevance in the interpretation of Ma'rifatullah verses in the Qur'an. The irfani approach is a method of acquiring knowledge based on spiritual experience, piety, and purification of the soul. Al-Ghazali, through his works such as Iḥyā 'Ulūm al-Dīn and Miṣbāḥ al-Hidāyah, places spiritual intuition (dzauq), divine tajalli and mujahadah as the primary foundation in attaining knowledge of Allah (ma'rifatullah). This study uses a qualitative method with a hermeneutic and descriptive-critical analysis approach to Al-Ghazali's works, by highlighting verses such as QS. Āli 'Imrān [3]: 190–191 and QS. Al-Baqarah [2]: 282, this study shows that the irfani approach offers a pattern of interpretation that combines the dimensions of reason, dhikr, and contemplation, thus going beyond the limits of textual interpretation that relies only on language and logic devices. The results of the study also confirm that Irfani epistemology has a significant contribution to the development of spiritual interpretation (isyari) and is very relevant to present a more holistic, transformative, and touching understanding of the Qur'an for Muslims.